GAMBARAN PENDERITA PENYAKIT ASAM URAT DI DUSUN KARANGLO SIDOMOYO GODEAN SLEMAN YOGYAKARTA - Nuryeti Syarifah; Ranty Fristaria (STIKES Wira Husada Yogyakarta, 2019)
Background: Gout is a disease characterized by sudden onset, and accompanied by arthritis which is very painful for the deposition of monosodium urate crystals or uric acid in the blood. The prevalence of gout in the world varies, between 2.3 to 17.6% and is increasing every year. Data Riskesdas 2018 the prevalence of gout in Yogyakarta increase from the year 2013 amounted to 3.5% to 4% in 2018.Objectives: Knowing the relationship with the family knowledge of prevention of recurrence of gout in the elderly in Hamlet Karanglo Sidomoyo Yogyakarta Sleman GodeanMethods:This research is quantitative with cross sectional design. The populationis the family that owns the elderly aged 55-80 years who suffered from gout and stay together amounted to 42 people. The sampling technique of total sampling and statistical tests using Gamma Test.Results: The results of this study the majority of respondents are knowledgeable both about gout as many as 29 respondents (69.0%) and the prevention of recurrence of gout well as much as 28 respondents (66.7%). Gamma test results showed that the significant value = 0.000 <0.05 with a correlation coefficient of 0.867.Conclusion: There is significant correlation between the knowledge of families with prevention of recurrence of gout in the elderly, with the strength of the relationship is very strong and positive correlation direction.